Happiness: a critical literature review - Mandishekwa, Robson (Research Journal of Economic and Management Studies, 2021)
The debate about what happiness is has been raging on for more than a century now. Without unanimity of definition though, the importance of happiness has manifested itself in the increase in happiness studies in journals and even in public policies. The study aims to bring a more unified definition by bringing together the main components involved in defining happiness. It also aims to highlight the importance of a working definition in happiness research. An outline of the operational definition helps identify whose happiness is being analysed. Findings from the systematic review of existing literature indicate that the debate still stands. Economists and positive psychologists, however, seem to concur that utility is a defining concept in happiness studies. Lastly, a group of authors seem to relegate to the peripheries the importance of the working definition of happiness in research yet this improves study evaluation. Thus, the misunderstanding of happiness is sometimes exacerbated by lack of the working definitions in some studies. The absence of operational definitions makes the question on whose happiness an important one to answer. The importance of indicating working definitions for controversial terms like happiness is recommended in this study